PERBANDINGAN SISTEM HUKUM PEMBUKTIAN DALAM PENANGANAN PERKARA TINDAK KORUPSI DENGAN PERKARA TINDAK PIDANA LAINNYA - Fira Mubayyinah (Al Hikmah: Jurnal Studi Keislaman, 2017)
Proof is one of a series conducted in the court process to seek the truth, proving a guideline in ways that justified the law remedy prove whether the defendant's right or wrong, Proof is also a provision governing evidence which justified the law and may be used to prove mistakes indicted judges (M. Yahya Harahap) KUHAP we have set in Article 183 "The judge must not convict someone unless at least two valid evidence he gained confidence that a crime actually occurred and that the defendant is guilty of doing it". From this article it can be seen that the judge's decision should be based on two (2) things: 1. A minimum of two items of evidence 2. From the evidence that judges gain confidence that the defendant is guilty of a criminal act. Becomes important we know the proof is in the general criminal law in this regard set out in the Criminal Code and specific criminal.